Chromosome-specific potential intron polymorphism markers for large-scale genotyping applications in pomegranate - Patil, Prakash Goudappa; Jamma, Shivani; N, Manjunatha; Bohra, Abhishek; Pokhare, Somnath; Dhinesh Babu, Karuppannan; Murkute, Ashutosh A.; Marathe, Rajiv A. (Frontiers in Plant Science, 2022)
Despite availability of whole genome assemblies, the identification and utilization of gene-based marker systems has been limited in pomegranate. In the present study, we performed a genome-wide survey of intron length (IL) markers in the 36,524 annotated genes of Tunisia genome. We identified and designed a total of 8,812 potential intron length (PIP) markers specific to 3,445 (0.12%) gene models that span 8 Tunisia chromosomes. The ePCR validation of all these PIP markers on Tunisia genome revealed single-locus amplification for 1,233 (0.14%) markers corresponding to 958 (0.28 %) genes. The markers yielding single amplicons were then mapped onto Tunisia chromosomes to develop a saturated linkage map. The functional categorization of 958 genes revealed them to be a part of nucleus and cytoplasm having protein binding and catalytic activity, and these genes are mainly involved in metabolic process including photosynthesis. Further, through ePCR 1,233 PIP markers were assayed on multiple genomes, which resulted in the identification of 886 polymorphic markers with an average PIC value of 0.62. In silico comparative mapping based on physically mapped PIP markers suggested higher synteny of Tunisia with Dabenzi and Taishanhong genomes (>98%) in comparison with the AG2017 genome (95%). We then performed experimental validation of a subset of 100 PIP primers on eight pomegranate genotypes and identified 76 polymorphic markers, with 15 having PIC values ≥ 0.50. We demonstrated the potential utility of the developed markers by analyzing the genetic diversity of 31 pomegranate genotypes using 24 PIP markers. This study reports for the first time large-scale development of gene-based and chromosome-specific PIP markers, which would serve as a rich marker resource for genetic variation studies, functional gene discovery and genomics-assisted breeding of pomegranate.